Elucidating the biogeographical variation of the venom of Naja naja (spectacled cobra) from Pakistan through a venom-decomplexing proteomic study - Wong, Kin Ying; Tan, Choo Hock; Tan, Kae Yi; Quraishi, Naeem H.; Tan, Nget Hong (Elsevier, 2018)
Naja naja is a medically important species that is distributed widely in South Asia. Its venom lethality and neutralization profile have been reported to vary markedly, but the understanding of this phenomenon has been limited without a comprehensive venom profile for the Pakistani N. naja. This study set to investigate the venom proteome of Pakistani N. naja applying reverse-phase HPLC, SDS-PAGE, mass spectrometry and data-mining approaches. The venom enzymatics and antigen binding activities were also studied. A total of 55 venom proteins comprising 11 toxin families were identified, with three-finger toxins (75.29%) being the predominant component, followed by phospholipase A2 (14.24%) and other proteins (< 5%). The enzyme activities of most of the venom components were also detected in this work. The high abundance of long neurotoxins (LNTX, 21.61%) in the Pakistani N. naja venom is varied from that reported for N. naja venoms from other geographical origins. The venom exhibited high immunoreactivity toward Naja kaouthia monovalent antivenom (NKMAV), which was raised against the LNTX-predominated heterologous Thai N. kaouthia venom. Together, the findings show that the Pakistani N. naja venom is predominated by LNTX, and this unique property correlates with its high lethality and effective neutralization by the heterologous NKMAV. Biological significance: This study reveals the compositional details of the venom proteome of Pakistani spectacled cobra (Naja naja). The protein subtypes, proteoforms, and relative abundances of individual proteins were comprehensively revealed in this study, following a venom decomplexing proteomic approach. The Pakistani cobra venom is unique among the rest of the N. naja venom composition reported thus far, as it contains a high abundance of alpha-neurotoxins (predominated by long neurotoxins); these are highly potent post-synaptic neuromuscular blockers that cause paralysis and are principal toxins that account for the high lethality of the venom (LD50 = 0.2 μg/g in mice). In contrast, previous reports showed that the N. naja venoms of India and Sri Lanka had a lower content of neurotoxins and a relatively higher value of LD50. The Pakistani cobra venom demonstrated sufficient immunoreactivity toward three antivenom products manufactured outside Pakistan (including the Indian product VINS), however the potency of antigen binding was the highest toward Naja kaouthia monovalent antivenom, a heterologous antivenom raised against a long neurotoxin-predominated venom of the Thai monocled cobra. From the practical standpoint, the findings indicate that the treatment of N. naja envenomation in Pakistan may be improved by the production of a locale-specific antivenom, in which the antivenom produced contains more antibodies that can target and react more specifically with the highly abundant lethal neurotoxins in the Pakistani N. naja venom.